Feasibility of delta radiomics–based pCR prediction for rectal cancer patients treated with magnetic resonance–guided adaptive radiotherapy - Wu, Junxiang; Xiao, Juan; Li, Yihong; Wu, Fan; Peng, Qian; Li, Churong; Tang, Bin; Orlandini, Lucia Clara (Frontiers in Oncology, 2023)
Magnetic resonance-guided adaptive radiotherapy (MRgART) represents the latest frontier in precision radiotherapy. It is distinguished from other modalities by the possibility of acquiring high-contrast soft tissue images, combined with the ability to recalculate and re-optimise the plan on the daily anatomy. The extensive database of available images offers ample scope for using disciplines such as radiomics to try to correlate features and outcomes. This study aimed to correlate the change of radiomics feature along the treatment to pathological complete response (pCR) for locally advanced rectal cancer (LARC) patients. Twenty-eight LARC patients undergoing neoadjuvant chemoradiotherapy (nCRT) with a short course (25Gy, 5 Gy x 5f) MRgART at 1.5 Tesla MR-Linac were enrolled. The T2 weighted MRI images acquired at each fraction, corresponding target delineation, pCR result of the surgical specimen and clinical variables were collected. Seven families of features (First order, Shape, GLCM, GLDM, GLRLM, GLSZM and NGTDM) were extracted and delta features were calculated from the ratio of features of each successive fraction to those of the first fraction. Wilcoxon-Mann-Whitney test and LASSO were utilized to reduce the dimension of features and select those features that are most significant to pCR. At last, the radiomics signatures were established by linear regression with the final set of features and their coefficients. A total of 581 radiomics features were extracted and 2324 delta features were calculated for each patient. Nineteen features and delta features, and one clinical variable (cN) were significant (p < 0.05) to pCR; seven predictive features were further selected and included in the linear regression to construct the radiomics signature significantly discriminating pCR and non-pCR groups (p < 0.05). Delta features based on MRI images acquired during a short course MRgART could potentially be used to predict treatment response in LARC patients undergoing nCRT.